Pulmonary thromboendarterectomy for chronic thromboembolic pulmonary hypertension: a systematic review - Brookes, John D. L.; Li, Crystal; Chung, Sally T. W.; Brookes, Elizabeth M.; Williams, Michael L.; McNamara, Nicholas; Martin-Suarez, Sofia; Loforte, Antonio (Annals of Cardiothoracic Surgery, 2022)
Background: Pulmonary thromboendarterectomy (PTE) is the gold standard treatment for patients with chronic thromboembolic pulmonary hypertension (CTEPH). However, the results are poorly quantified outside a few registry reports and several individual centers. Methods: A systematic review was performed searching five electronic databases assessing the outcomes for adult patients undergoing PTE for CTEPH. All articles that reported mortality data were included. Primary outcome measures were early/inpatient mortality; secondary outcomes were survival, pulmonary haemodynamics, morbidity and functional status following PTE for CTEPH. Results were pooled via a meta-analysis of proportions and meta-regression. Results: A total of 5,717 studies were identified, yielding sixty-one relevant papers. Thirty-day mortality ranged from 0.8% to 24.4%, and on meta-analysis was 8.4% [95% confidence interval (CI): 7.2–9.6%]. Mortality was noted to decrease with increasing center volume of PTE cases (P